PLANT-BASED NEW FOOD PRODUCT DEVELOPMENT: From Conception to Implementation of “Banana Blossom Jerky” - Tiffany Aileen; Gareth Currie (Jurnal Hospitality dan Manajemen Jasa, 2019)
Abstrak: Penelitian ini bertujuan untuk mengukuhkan, meneliti, dan mengevaluasipengembangan “Banana Blossom Jerky” melalui model New Product Development(NPD). Penelitian sekunder mengenai target pasar lebih dahulu dilakukan untukmembantu pengembangan dan konseptualisasi produk. Penelitian utama dilakukandengan metode kombinasi dan dianalisis dengan triangulasi data. Tujuh Milenial dariberbagai kota di Indonesia dan dua ahli NPD dipilih sebagai sampel oleh penulismelalui purposive sampling. Konsep makanan plant-based ini diterima oleh generasiMillenial Indonesia yang terbukti tertarik pada makanan sehat.Kata Kunci: Jantung Pisang, Makanan Plant-based, Milenial, New ProductDevelopment.Abstract: This research aimed to justify, research, and evaluate the development of“Banana Blossom Jerky” through New Product Development (NPD) model.Secondary research pertains target market was first conducted to assist thedevelopment and conceptualization of the product. The primary research wasconducted through mixed method and analyzed with data triangulation. SevenMillennials from different cities in Indonesia and two experts in NPD were chosen asthe samples by the author through purposive sampling. The concept of this plant-basedfood is found to be filling the market gap for Indonesian Millennials that proven to beinterested in healthy foods.Keywords: Banana Blossom, Plant-based Food, Millennials, New ProductDevelopment.